Possible role of pre-vaccination T-lymphocyte subpopulations in the antibody response to COVID-19 vaccines in children undergoing chemotherapy - Péterfia, Csaba; Komlósi, Zsolt I.; Pós, Zoltán; Lupsa, Nikolett; Fekete, Nóra; Böröcz, Katalin; Dergez, Timea; Leibinger, Evelin A.; Benedek, Noémi; Vojcek, Ágnes; Horváth, Bence; Vertike, Vita; et al. (Frontiers in Immunology, 2026)
BackgroundIn a previous study, we found a possible connection between pre-vaccination CD3+CD56+ T cells and seroresponse to influenza vaccination in immunosuppressed patients. Decreased circulating CD3+CD56+ T cells have been described in severe COVID-19, but their role in vaccination is unknown. This study evaluated the humoral immune response after SARS-CoV-2 vaccination in children with cancer following two doses of the BNT162b2 mRNA vaccine. We investigated the relationship between cellular immunity (including CD3+CD56+ T cells) and the post-vaccination antibody response.MethodsA multicenter, prospective cohort study was completed by recruiting patients receiving chemotherapy and healthy controls, who received two doses of the BNT162b2 mRNA vaccine. Flow cytometric analysis of peripheral blood lymphocyte subpopulations was performed before vaccination; serum anti-SARS-CoV-2 IgG was measured before vaccination and 21–28 days after the second vaccination. We evaluated the relationship between various cellular parameters before vaccination and antibody response.ResultsSerological response was assessed in 20 oncology patients and 13 healthy controls. The seroconversion rate was 55% among oncology patients and 92.3% among healthy controls (p = 0.023). Geometric mean fold increase (GMFI) of the titers was 6.69 and 41.64 (p = 0.011), respectively. Flow cytometric analysis revealed a significantly higher seroconversion rate in patients with higher baseline CD3+CD56+ T cell (p = 0.044) and CD56+ NK (p = 0.038) cell counts. Based on GMFI, we found a positive association between a greater antibody response and higher baseline CD4+ (p = 0.007), CD4+CD3+CD56+ (p = 0.019), and CD4+ MAIT (p = 0.010) cell counts, as well as a higher CD4/CD8 ratio (p = 0.029).ConclusionOur study suggests that an adequate humoral immune response can be induced by the SARS-CoV-2 mRNA vaccine in pediatric oncology patients. We explored for the first time the possible association between pre-vaccination T lymphocyte subpopulations (CD3+CD56+, CD56+ NK, CD4+, CD4+CD3+CD56+ cells) and the antibody response to the COVID-19 vaccine. We have similar observations as previously reported with influenza vaccination, suggesting that CD3+CD56+ T cells may be involved in the immune response to SARS-CoV-2 vaccines. We highlight the connection between pre-vaccination CD4+ MAIT cell populations and the antibody response.